Development and content validation of the Telenursing Interaction and Satisfaction Questionnaire (TISQ) - Marie Mattisson (Health Expectations, 2019)
Abstract Background Caller satisfaction with telephone advice nursing (TAN) is generally high, and the interaction is essential. However, a valid questionnaire exploring caller satisfaction in TAN with focus on perceived interaction is lacking. Objective To develop and assess content validity and test‐retest reliability of a theoretically anchored questionnaire, the Telenursing Interaction and Satisfaction Questionnaire (TISQ), that explores caller satisfaction in TAN by focusing on perceived interaction between the caller and the telenurse. Methods The study was performed in three stages. First, variables relevant for patient satisfaction in health care were identified through a literature search. Variables were then structured according to the Interaction Model of Client Health Behavior (IMCHB), which provided theoretical guidance. Items relevant for a TAN context were developed through consensus discussions. Then, evaluation and refinement were performed through cognitive interviews with callers and expert ratings of the Content Validity Index (CVI). Finally, test‐retest reliability of items was evaluated in a sample of 109 individuals using intraclass correlation coefficients (ICC). Results The TISQ consists of 60 items. Twenty items cover perceived interaction in terms of health information, affective support, decisional control and professional/technical competence. Five items cover satisfaction with interaction and five items overall satisfaction. Remaining items reflect singularity of the caller and descriptive items of the call. The TISQ was found to exhibit good content validity, and test‐retest reliability was moderate to good (ICC = 0.39‐0.84). Conclusions The items in the TISQ form a comprehensive and theoretically anchored questionnaire with satisfactory content validity and test‐retest reliability.